The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00702-020-02156-4
|View full text |Cite|
|
Sign up to set email alerts
|

Smell and taste in cervical dystonia

Abstract: The pathophysiology of cervical dystonia is not completely understood. Current concepts of the pathophysiology propose that it is a network disorder involving the basal ganglia, cerebellum and sensorimotor cortex. These structures are primarily concerned with sensorimotor control but are also involved in non-motor functioning such as the processing of information related to the chemical senses. This overlap lets us hypothesize a link between cervical dystonia and altered sense of smell and taste. To prove this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 71 publications
(120 reference statements)
0
24
0
Order By: Relevance
“…Clinical parameters, such as the degree of cervical dystonia, did not predict olfactory decline. Non-motor manifestations of dystonia, such as cognitive and psychiatric alterations, which potentially impact the performance of olfactory tests [ 161 , 164 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ], were not assessed as co-factors in this study.…”
Section: Olfactory Deficits In Dystonia: the Current Statementioning
confidence: 99%
See 3 more Smart Citations
“…Clinical parameters, such as the degree of cervical dystonia, did not predict olfactory decline. Non-motor manifestations of dystonia, such as cognitive and psychiatric alterations, which potentially impact the performance of olfactory tests [ 161 , 164 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ], were not assessed as co-factors in this study.…”
Section: Olfactory Deficits In Dystonia: the Current Statementioning
confidence: 99%
“…To comprehensively assess the chemical sense in dystonia, a more recent study appraised the sense of smell, as well as the sense of taste in subjects with cervical dystonia, which was compared to carefully matched healthy controls ( Table 1 ) [ 161 ]. Moreover, cognitive and psychiatric alterations as non-motor manifestations of dystonia were assessed by the use of an extensive test battery.…”
Section: Olfactory Deficits In Dystonia: the Current Statementioning
confidence: 99%
See 2 more Smart Citations
“…Because of the anatomical overlap of structures involved in the pathophysiology of idiopathic BSP and the chemical senses, an impairment of the sense of smell and taste may be found in subjects with idiopathic BSP. This idea is supported by diminished chemical senses in subjects with cervical dystonia (CD) (Marek et al 2018 ; Herr et al 2020 ), where alterations in the sensorimotor control network are also found (Jinnah et al 2013 , 2017 ). Although largely overlooked, the chemical senses fulfill fundamental aspects important for daily life (Croy et al 2014 ; Doty 2019 ).…”
Section: Introductionmentioning
confidence: 98%